PENERAPAN PRINSIP - PRINSIP GOOD GOVERNANCE DALAM PEMBUATAN E â€“KTP DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN MINAHASA UTARA - SASUNDAME, REINALDI GISBERD; Tulusan, Femmy; Kalangi, Jhonny (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRAK Governance is a form of good governance and solid state responsible, and transparent, responsive, accountable, efficient and effective. Office of Population and civil registry offices of North Minahasa Regency is directly related to the community, especially in the service of making Identity card Electronic. To create a good public service and thorough then there must be good cooperation of all elements of good leadership, employees and the community. good governance principles into concrete solutions to create a good public service.The purpose of this study was to clarify the application of good governance in the public service in particular the manufacture of Identity card ElectronicPopulation and civilian agencies of North Minahasa Regency.Â This research method is descriptive qualitative method. The primary data sourced from informants consisting of a first element of the leadership of the Department, employees of service providers and the elements of the last elements of the public service recipient. How data retrieval is done with interviews using interview guide later on though using data reduction, data presentation and conclusion and verification of data.The results showed that the application of the indicators of good governance: participation, rule of law, transparency, responsiveness, effectiveness and efficiency, and accountability in the Department of Population and Civil North Minahasa Regency, especially in service of making Identity card Electronichas not gone well. It is evident there are still many problems that arise, for example the department is still lacking in socializing the public about the importance of Identity card Electronicwhere there are 37 781 North Minahasa Regency community who do not have Identity card Electronic or are still about 23 percent. Socialization rules and standard operating procedures to the public is still very lacking, transparency and accountability of services to the community is also not a good society is still very difficult to access information from the department both in terms of administration, standard operating procedures, service flow, costs, turnaround time. Besides the professionalism and discipline of employees in providing services that impressed still not good so the practice of nepotism, extortion and grativikasi still very angry arise, this is certainly caused by the supervision of the leadership is still lacking, not to mention talk about the facilities and funding limited becomes a serious problem.Based on the results of research and discussion, it can be concluded that the application of the principle - the principle of good governance in the department of population and civil registration Minahasa regency north, especially in service of making E KTP has not gone well. To improve this it is advisable to. The important thing also is establishing cooperation with the village government in this case coconut village up to the head of the environment that they could deliver the socialization directly to the people in their village. convey to the public in question at the start of the management fees, Flow Services, the completion time, the procedure, until the necessary administrative requirements. Additionally Before the firmness of the leadership offices to oversee the rules besides firmness rules should also be important, other than that the rules are made to be accompanied by strict sanctions eg cutting allowance doubt, a rebuke from the head, to the penal sanctions. the need for data collection back in North Minahasa people to get accurate data on the validity of the agency should be involved to the village and head guard in the record, it is considered important because they are in direct contact with people. The forest service can pick up the ball by holding the recording service Identity card Electronicin each making district in the county north Minahasa in cooperation with the village. This is to curb the high number of North Minahasa community presentation that does not have Identity card Electronic.